Analysis of the localization and timing of the hernias formation in anterior abdominal wall after colostomy - K.I. Sergatskiy; V.I. Nikol'skiy; V.S. Romanova; A.V. Korobov; V.E. Kiselev (Известия высших учебных заведений. Поволжский регион: Медицинские науки, 2023)
Background. Despite the many studies conducted, the problem of choosing the prevention of parastomal hernias remains relevant. Nowadays, no studies have been presented in the available literature on the timing of the parastomal hernias formation after removal of the colostomy and localization of the hernia in the projection of the intestinal stoma. The purpose of this study is to evaluate the results of stoma treatment to establish the average time of formation of parastomal hernia and its localization in the projection of the intestinal stoma. Materials and methods. The analysis of 22 patients with various abdominal surgical pathology requiring removal of a colostomy in 2017‒2022, who subsequently developed a parastomal hernia, was carried out. Results. The study did not establish a statistically significant difference in the timing of the formation of parastomal hernia. A statistically significant difference was obtained among patients with different localization (lateral-caudal and circular location) (p < 0.05) of parastomal hernia. Conclusions. The revealed fact of the formation of parastomal hernias in the absolute majority of cases, lateralcaudal localization, directs the surgeon to perform preventive measures to further strengthen this zone in order to prevent hernias during the formation of a colostomy.